A comparison of the water absorption and water solubility values of four different composite resin materials - Cangül, Suzan; Adigüzel, Özkan; Tekin, Samet; Öztekin, Faruk; Satici, Ömer (Cumhuriyet University Faculty of Dentistry, 2018)
Objectives: The aim of this study was to compare the water absorption and water solubility of four different composte resin materials. Materials and Methods: A total of 40 cylindrical discs were prepared and polymerised with light, as 10 from each group, each sample 2 mm in depth and 8 mm in diameter. The samples were kept for 24 hrs in a dessicator until a stable weight was reached. Then, the weight of each sample was measured on highly sensitive scales. To calculate the water absorption and solubility, measurements were made again with the sensitive scales at the end of 1, 7 and 30 days. The data obtained were evaluated with One-Way ANOVA variance analysis and the Friedman test. Results: As a result of the statistical analyses, significant differences were determined between the composite resins in respect of water absorption on days 7 and 30 and in respect of solubility on day 30 only (p < 0.05). Conclusion: When the water absorption and water solubility of composite resins at the end of 30 days were evaluated statistically, it was observed that Ceram X One material showed the lowest values. This is related to the structure of the restorative material. It can be concluded that the negative mechanical, physical and biological effects created by the water absorption and water solubility factors of restorative materials are important issues that should be taken into consideration. © 2018 Cumhuriyet University Faculty of Dentistry.; Amaç: Bu çalişmanin amaci estetik amaçli kullanilan dört farkli kompozit rezinin su emilimi ve sudaki çözünürlüklerinin karşilaştirilmasidir. Gereç ve Yöntemler: çalişmada her kompozit grubundan 10 tane olmak üzere 2 mm derinliğinde 8 mm çapinda toplam 40 adet silindirik disk hazirlandi ve işikla polimerize edildi. örnekler sabit ağirliklarina ulaşincaya kadar 24 h desikator icinde bekletildi. Daha sonra tüm örneklerin ağirliklari hassas terazi ile ölçüldü. 1, 7 ve 30. günlerin sonunda su emilimini ve çözünürlük sonuçlarini hesaplamak için hassas terazi ile tartimlar yapildi. Elde edilen veriler ANOVA tek yönlü varyans analizi ve Friedman testleri kullanilarak değerlendirildi. Bulgular: Yapilan istatistikler sonucunda kompozit rezinlerin su emiliminde 7. ve 30. günlerde, sudaki çözünürlüklerinde ise sadece 30. günde anlamli farkliliklarin olduğu saptanmiştir (p < 0,05). Sonuç: Kompozit rezinlerin 30 gün sonundaki su emilimi ve suda çözünürlüğü istatistiksel açidan değerlendirildiğinde Ceram X One materyalinin en düşük değerleri gösterdiği görülmüştür. Bu da restoratif materyalin yapisi ile ilişkilidir. Sonuç olarak restoratif materyallerin su emilimi ve suda çözünürlük faktörleri, mekanik, fiziksel ve biyolojik olarak olumsuz etkiler oluşturduğundan gözönünde bulundurulmasi gereken önemli konulardandir. © 2018 Cumhuriyet University Faculty of Dentistry.
Dört farkli kompozit materyalinin su emilim ve çözünürlük değerlerinin karşilaştirilmasi
Keywords: Composite resin; Kompozit rezin; Su emilimi; Sudaki çözünürlük; Water absorption; Water solubility